2006
DOI: 10.1016/j.jacc.2006.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Transplantation Shows Superior Atheroprotective Effects of Gene Therapy With Apolipoprotein A-I Milano Compared With Wild-Type Apolipoprotein A-I in Hyperlipidemic Mice

Abstract: Macrophage-specific expression of the apoA-IMilano gene is more effective than wild-type apoA-I in reducing atherosclerosis and plaque inflammation despite comparable circulating levels of the transgene and lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 22 publications
4
44
0
1
Order By: Relevance
“…This conclusion is supported by recent findings in apoA-I/apoE doubleknockout mice, in which the expression of apoA-I M leads to enhanced macrophage cholesterol efflux and reduced arterial monocyte infiltration, thus lowering atherosclerosis burden, compared with mice expressing wild-type apoA-I. 32 Low plasma HDL-C concentrations are highly prevalent in coronary patients, and genetic variation in HDL candidate genes accounts for a sizable proportion of low HDL-C in the general population. 33 Genetically determined low-HDL states, however, may be associated with an extremely variable atherosclerosis burden 34 and coronary risk.…”
Section: Gomaraschi Et Al Vascular Function In Apoa-i M Carrierssupporting
confidence: 66%
“…This conclusion is supported by recent findings in apoA-I/apoE doubleknockout mice, in which the expression of apoA-I M leads to enhanced macrophage cholesterol efflux and reduced arterial monocyte infiltration, thus lowering atherosclerosis burden, compared with mice expressing wild-type apoA-I. 32 Low plasma HDL-C concentrations are highly prevalent in coronary patients, and genetic variation in HDL candidate genes accounts for a sizable proportion of low HDL-C in the general population. 33 Genetically determined low-HDL states, however, may be associated with an extremely variable atherosclerosis burden 34 and coronary risk.…”
Section: Gomaraschi Et Al Vascular Function In Apoa-i M Carrierssupporting
confidence: 66%
“…It was previously shown that macrophage apoAI reduces the levels of infl ammatory monocyte/macrophages in the aortic lesion ( 11,14 ). Figure 2A and B show lesion composition analyses, with apoAI recipient mice having significantly fewer CD3 + (7.0 ± 3.7% vs. 9.9 ± 2.6% in control recipients) and CD4 + (7.4 ± 3.0% vs. 12.3 ± 2.0% in control recipients) cells in the proximal aorta, respectively.…”
Section: Macrophage Apoai Expression Reduced Levels Of T Cells In Aormentioning
confidence: 96%
“…Together, lipid-free apoAI, HDL-bound apoAI, and apoE act in synergy to extract cholesterol from macrophages, thus infl uencing both macrophage cholesterol accumulation, a hallmark of atherosclerosis, and macrophage phenotype adjustment to local infl ammatory impulses ( 18,19 ). Both macrophage and exogenous apoAI expression also reduce cytokine expression by macrophages and promote the switch to an anti-infl ammatory macrophage phenotype ( 11,20,21 ).…”
Section: Analysis and Quantitation Of Arterial Lesionsmentioning
confidence: 99%
“…An apoA-I M knockin mouse strain was crossed with an atherosclerosis-susceptible human apoB/apoA-II mouse model, and apoA-I M was found to have no protective advantage over WT apoA-I (23). However, a study in which bone marrow transplantation in apoA-I and apoE doubleknockout mice using bone marrow that had been transduced with a retroviral vector expressing WT apoA-I or apoA-I M demonstrated that apoA-I M reduced atherosclerosis to a greater extent than WT apoA-I (19). However, when LDL receptor-deficient mice were infected with AAV expressing either WT apoA-I or apoA-I M and fed a Western diet for 8 weeks, there was no difference in lesion development (24).…”
Section: Effects Of Mutations Of R173 In Apoa-i On Hdl Compositionmentioning
confidence: 99%
“…Despite a lipid profile that is usually associated with a high risk of premature cardiovascular disease, apoA-I M carriers display no increase in cardiovascular disease or events (10,14,15). This has led to speculation that apoA-I M is a gainof-function mutation that has enhanced cardio-protective effects (16)(17)(18)(19)(20)(21)(22), while others believe that wild-type (WT) apoA-I and apoA-I M are functionally equivalent (23,24). A clinical trial of repeated intravenous infusions of apoA-I M -phospholipid complexes demonstrated regression of existing atheromas after five weekly treatments (25,26).…”
mentioning
confidence: 99%